2020
DOI: 10.3389/fspor.2020.574854
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine and Exercise Performance: Possible Directions for Definitive Findings

Abstract: Caffeine is one of the most studied supplements in the world. Studies correlate its use to increased exercise performance in endurance activities, as well as its possible ergogenic effects for both intermittent and strength activities. Recent findings show that caffeine may increase or decrease exercise performance. These antagonist responses may occur even when using the same dosage and for individuals with the same characteristics, making it challenging to explain caffeine's impact and applicability. This re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
55
0
9

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 141 publications
0
55
0
9
Order By: Relevance
“…However, even though they have the same genotypes, it has been suggested that females require a longer time to metabolize CAF than males [ 15 ]. This fact could be explained by the greater half-life of CAF in females than in males [ 14 ]. Moreover, the effect of CAF was reported to be greater in individuals with larger muscle mass [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, even though they have the same genotypes, it has been suggested that females require a longer time to metabolize CAF than males [ 15 ]. This fact could be explained by the greater half-life of CAF in females than in males [ 14 ]. Moreover, the effect of CAF was reported to be greater in individuals with larger muscle mass [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…This difference could be related to the methodological and the inter-individual variations. In fact, the ergogenic effects of CAF are influenced by participants’ characteristics (i.e., sex, age, training status), CAF supplementation protocol (i.e., dose, form, ingestion time, time of day of CAF supply), tolerance to CAF, genetics, and nature of exercise [ 3 , 7 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the recent review of caffeine in the context of athletic performance published by Martins et al [128] improvements in performance were noted at doses of 2-9 mg/kg. This is notable because the physiological mechanisms that are involved when the dose is increased remain unclear, since the subject's regular consumption and the time of day when the caffeine is taken may have positive or negative effects on the ensuing benefits.…”
Section: Energy Drinks Genetics and The Relationship With Athletic mentioning
confidence: 99%
“…Some authors defend its use a high dose only on the competition's day, after a withdrawal from any CAF source during the training period, since it is hypothesized that this strategy could enhance its ergogenic effect [18][19][20] . On the other hand, despite the ndings of studies [21][22][23] that indicate tolerance to ergogenic effects with the regular use of CAF, other authors recommend the use of doses that represent an average amount of caffeine above the usual (i.e., reducing the tolerance effect), having its ergogenic effect potentiated 4,5 .…”
Section: Introductionmentioning
confidence: 99%